2013
DOI: 10.1186/1477-7819-11-232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course for patients with peritoneal carcinomatosis excluded from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy

Abstract: BackgroundCytoreductive surgery combined with 'Hyperthermic IntraPEritoneal Chemotherapy’ (HIPEC) represents the only potentially curative treatment available for carcinomatosis secondary to colorectal cancer (CRC), pseudomyxoma peritonei (PMP), malignant peritoneal mesothelioma (MM) and goblet cell carcinoma (GCC). Despite preoperative investigation some patients are excluded perioperatively because of unacceptably massive tumor extent. The data available on the clinical course of these patients are sparse. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…19.5%, respectively. The summarized HIPEC-related mortality and morbidity in 48 articles (the total number of patients, n = 4,809) [ 12 , 16 , 20 , 35 , 36 , 38 , 39 , 46 , 48 - 50 , 52 - 54 , 56 , 58 - 62 , 64 - 69 , 71 , 73 , 75 , 76 , 79 , 80 , 82 - 90 , 92 , 100 - 104 ] were 2.8% (SD, ± 2.9%; range, 0-12%) and 33.0% (SD, ± 13.4%; range, 4-60%), respectively. Some large-sample retrospective studies and population-based analysis found a series of approximate results that the range of mortality was 2%-5.6% and morbidity was 25%-34% [ 93 - 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…19.5%, respectively. The summarized HIPEC-related mortality and morbidity in 48 articles (the total number of patients, n = 4,809) [ 12 , 16 , 20 , 35 , 36 , 38 , 39 , 46 , 48 - 50 , 52 - 54 , 56 , 58 - 62 , 64 - 69 , 71 , 73 , 75 , 76 , 79 , 80 , 82 - 90 , 92 , 100 - 104 ] were 2.8% (SD, ± 2.9%; range, 0-12%) and 33.0% (SD, ± 13.4%; range, 4-60%), respectively. Some large-sample retrospective studies and population-based analysis found a series of approximate results that the range of mortality was 2%-5.6% and morbidity was 25%-34% [ 93 - 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor prognosis for those undergoing aborted procedures, one would expect patients to suffer a rapidly progressive clinical course. Rodt and colleagues noted, however, that a nontherapeutic laparotomy did not negatively impact the clinical course of those found to have advanced disease precluding successful completion of CRS/HIPEC (14). In their series, the median survival was 12.7 months for colorectal cancer patients and 88% of patients received palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…The primary reason behind aborted CRS is widespread abdominal disease, why one can expect those patients to suffer a rapidly progressive and lethal clinical course [22]. In the series by Rodt et al, the median survival in corresponding situations was 12.7 months, whereas others have reported that only about half of the patients who underwent aborted CRS procedures went on to receive palliative chemotherapy associated with a survival of only 8 months [23]. The Dutch group likewise observed that similar patients fared a dismal prognosis with a median survival of 11.2 months in these situations even for patients treated with palliative chemotherapy compared to only 2.7 months for those with best supportive care alone [21].…”
Section: Discussionmentioning
confidence: 99%